Evaluation of supporting role of early enteral feeding via tube jejunostomy following resection of upper gastrointestinal tract - Ghafouri, Ali (Tehran University of Medical Sciences, 2012)
BACKGROUND: Today, early diagnosis of upper gastrointestinal (GI) tract malignancies and their surgical resection is becoming more feasible. One of the important side effects in upper GI tract malignancies is malnutrition which has direct relationship with postoperative complications. Nonetheless, there is no easy regimen of nutrition for these patients especially for the first week after operation. Accordingly we present a simple method for improving feeding such patients via tube jejunostomy. The aim of this study was to investigate the impact of early enteral feeding (EEF) on postoperative course after complete resection of upper gastrointestinal tract malignancy and reconstruction. METHODS: Between September 2005 to September 2008, 60 consecutive patients (22 female, 38 male) with upper GI tract malignancies who had undergone complete resection and reconstruction enrolled in this study. The patients randomly divided equally in two groups of control and EEF. Control group was treated with traditional management of nil by mouth and intravenous fluids for the first five postoperative days and then with liquids and enteral regular diet when tolerated. In EEF group the patients were fed by tube jejunostomy from 1(st) postoperative day and assessed for nutritional status before surgery and 5 days after surgery. Both groups were monitored on the basis of weight gain, clinical and paraclinical parameters and postoperative complications. RESULTS: Sixty patients were randomly divided to two equal groups. Surgical procedures were similar in two groups and no significant difference in demographic and basic nutritional status were found. On 5(th) postoperative day serum albumin was 4.2±0.4 g/dl in EEF and 3.6±0.3 g/dl in control group (p= 0.041). Also serum transferrin was 260.8±2.5 mg/dl and 208±1.8 mg/dl in EEF and control group respectively (p < 0.001). Moreover, hospital stay was shorter in EEF group (7.7±3.1 vs. 14±2.5 days, p = 0.009).There were four (13.3%) anasatomotic leakages in control group and one (3.3%) in EEF group (p = 0.353). Also there was six (20%) wound infection in control group and three (10%) in EEF group (p = 0.472). CONCLUSION: The EEF by tube jejunostomy can be an effective method of feeding patients in postoperative days of resection of GI malignancies. Postoperative hospital stay would be shorter and the level of laboratory parameters especially serum transferrin is higher in EEF in comparison with control group. It also may reduce postoperative complications such as wound infection and enterocutaneous fistula.